2018
DOI: 10.1016/s2542-5196(18)30167-0
|View full text |Cite|
|
Sign up to set email alerts
|

Linking sustainability to the healthy eating patterns of the Dietary Guidelines for Americans: a modelling study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 17 publications
10
100
0
1
Order By: Relevance
“…This finding underscores the large difference in impacts across meat types and not all "meat-containing" meals should be assumed to be more impacting than meatless meals-especially meatless meals containing other animal products (e.g., dairy). Other recent studies have done a thorough investigation that involves disaggregating food types and have come to similar conclusions as our study with respect to both magnitude of impacts and predominating contributors to US dietary impacts [60,61].…”
Section: Uncertainty Assessmentsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding underscores the large difference in impacts across meat types and not all "meat-containing" meals should be assumed to be more impacting than meatless meals-especially meatless meals containing other animal products (e.g., dairy). Other recent studies have done a thorough investigation that involves disaggregating food types and have come to similar conclusions as our study with respect to both magnitude of impacts and predominating contributors to US dietary impacts [60,61].…”
Section: Uncertainty Assessmentsupporting
confidence: 79%
“…The uncertainty regarding how to treat beverages when considering meals is tied to the reality that different beverages serve different functions in the diet, which are subjectively "part of a meal" or not. Diet-level studies offer a more holistic vision of the impact of beverages; for example, in Heller et al (2018) beverages were a non-negligible source of impact in the US diet [60].…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
“…If the diet is high-fat, more land is required [27]. A study from the USA by Blackstone et al found that the vegetarian diet has the lowest GHGEs and is favorable when it comes to sustainability [28].…”
Section: Land Use For Production Of Lov Dietsmentioning
confidence: 99%
“…Ridoutt et al [32] examined a conventional and healthy diet scenario from a nutritional balance and import reliance perspective based on linear projections for national agricultural production. Blackstone et al [36] investigated the environmental impacts of different recommended healthy dietary patterns in the US context. As of yet, however, no study has investigated both multiple environmental impacts and direct food availability implications of alternative diets based on more complex, non-linear agricultural production projections at a national or regional level, which is necessary to give a more comprehensive picture of food, sustainability and health issues.…”
Section: Introductionmentioning
confidence: 99%